Development of an advanced nano-satellite (VELOX-IV) : power supply system - Sha, Lin (2016)
The satellite research centre of NTU has successfully completed six satellite programs. Among them, VELOX-I and VELOX-II are classified as nano-satellites, i.e. satellites that weight between 1 and 50kg. For VELOX power supply system (PSS), it includes photovoltaic array (PV), battery management system (BMS) and power conversion and distribution (PCM/PDM) module. As with any power equipment, these systems are limited by the rated power. The maximum rated power of the step-down converter in VELOX-II is 30W or 6A. The objective of this final year project is to propose a modular power supply system (PSS) for a nano-satellite. The modular PSS can overcome the rated power limitation of equipment. This will help in reducing the development time further by allowing the scale-up of required power for future satellite programme. The proposed modular PSS consists of one power control module and several decision modules to implement power conversion/distribution and battery management functions. Each decision module of the PSS is controlled by single microcontroller and able to do decision making. The power control module is the brain of the whole PSS to control all decision modules. The control process is achieved through intra-satellite communication system. The controller area network (CAN) protocol is selected for the intra-satellite communication system due to its competency as compared with other communication types. The data transmission speed of the CAN bus is much higher and robust as compared to I2C and SPI. It reduces the wiring of the system significantly. All the messages from each module are transmitted through the CAN bus. The CAN message protocol is designed to make the PSS intelligent as every module can receive the correct message and discard the non-related or error message. The speed of the data transmission is up to 500Kbps which has been tested with the prototype implemented on the breadboard. The power conversion module is able to implement the MPPT function with efficiency of 86% and 83% by using P&O and InC algorithm respectively. The efficiency of the boost converter is approximately 87%. Testing is conducted at room temperature (25°C) by changing different parameters.